Strategi Guru PAI Dalam Membimbing Pengamalan Ajaran Agama Islam Pada Siswa SDN 2 Galagamba Ciwaringin Cirebon - Surtini, Surtini; Na’imah, Farida Ulvi; Muslihun, Muslihun (Program Studi Pendidikan Agama Islam, 2023)
This research aims to analyze the learning strategies used by teachers in guiding the practice of Islamic teachings among students at SDN 2 Galagamba. This research is qualitative research with a case study approach. Data was collected through observation, interviews, and documentation. The research results show that teachers use a variety of learning strategies, methods, and techniques, such as card match, reading aloud, card sorting, inquiry, group discussion, simulation, demonstration, and